Pengaruh Kombinasi Latihan Plyometric Unilateral dan Bilateral terhadap Power Tungkai Atlet Futsal Remaja - Yaris Zulfan Ibrahim; Dikdik Zafar Sidik; Geraldi Novian (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to examine the effect of combined unilateral and bilateral plyometric training on leg power improvement in adolescent futsal athletes. A pre-experimental one-group pretest-posttest design was used, involving 21 male futsal extracurricular athletes aged 15–18 years at SMAN 1 Padalarang, selected through purposive sampling. The combined unilateral-bilateral plyometric program was administered for six weeks with 16 sessions, and leg power was measured using the triple hop jump test. The Paired Sample t-Test showed a significance value of 0.000 (p < 0.05) for both left and right legs, with mean increases of 0.28 m (4.40%) on the left leg and 0.25 m (3.85%) on the right leg. It is concluded that combined unilateral and bilateral plyometric training significantly improves leg power in adolescent futsal athletes and can serve as an alternative physical training program in futsal extracurricular coaching.   Keywords: Adolescent Athletes, Bilateral Plyometric, Futsal, Leg Power, Unilateral Plyometric.